An exploration of students’ engagement in EFL classrooms - Ivana Sambara Barus; Fadlia Fadlia; Merina Devira (Universitas Syiah Kuala, 2022)
The purpose of this research was to explore students' behavioral engagement in the classroom and the factors that affect it. This research was approached using an explorative descriptive qualitative study., involving teachers and students in two classes at the first grade of a senior high school in Langsa, Indonesia. The classes were taught by two English teachers, and 57 students were involved. The instruments used in this research were observations, questionnaires and focus group discussions with teachers and students. The results of this study indicate that most students paid serious attention to the lesson, put their best effort to focus on the teaching and learning process, and complete assignments. In addition, the students were active in asking questions, giving opinions, and participating in group discussion. The results of this study also show that the most dominant factor in influencing students 'engagement was the teachers' support factor, followed by class structure and school level factors. Therefore, it is suggested that English teachers and school provide best support to students, and they establish good class structure in terms of class size and situation to improve students’ engagement.